PENGEMBANGAN TES FORMATIF BERORIENTASI HOTS PADA MATERI TERMOKIMIA KELAS XI IPA DI SMAN SAMBAS - Sri Maryati; Hairida Hairida; Rachmat Sahputra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the feasibility and the response has of teachers to formative tests oriented Higher Order Thinking Skills (HOTS) on thermochemical materials. This research is development research (R&D) that referring to an addie development model adapted by an analysis, a design, Development, and the evaluation. The feasibility assessment of development results is the carryout by material experts and evaluations as well as linguists. Based on the results of data analysis, it can be concluded that hotsoriented formative tests are reviewed from the validity of the material and the evaluation and the language is considered very feasible with a percentage of 100%. The teacher a response to the development results was excellent with a percentage of 85.19%. The results of this study are very feasible for teachers to use in the evaluation of learning on thermochemical materials.Keywords: A formative Test, HOTS, Thermochemical, ADDIE.